Bentuk Partisipasi Masyarakat Dalam Pengelolaan Sampah Rumah Tangga Di Kecamatan Banjarmasin Selatan - Lina Nabila; Sidharta Adyatma; Eva Alviawati; Aswin Nur Saputra; Nevy Farista Aristin (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This research aims to identify forms of community participation in managing household waste in South Banjarmasin District. The research method uses descriptive quantitative. Respondents in the study totaled 232 heads of families. The data used in the research are primary data and secondary data. Primary data is in the form of observations and questionnaires, secondary data is sourced from the Environmental Service, Banjarmasin City Central Statistics Agency and the South Bajarmasin District Government. Community participation in household waste management in South Banjarmasin District includes five parameters of forms of participation, namely thoughts, energy, assets and skills and abilities. The results of the research show that from 4 sub-districts in South Banjarmasin District, namely Kelayan Selatan, Pekauman, Kelayan Tengah and Tanjung Pagar, the first form of participation is the form of property participation in the form of active community members paying fees to the waste officers every 4 weeks ranging from IDR 4,000-20,000 . The second most common form of participation is the form of participation from the idea of knowing about waste management in the waste bank from the RT head, through information on waste management, the community participates in depositing waste every 2 weeks to the waste bank. The third most common form of participation is the form of labor participation in sorting organic waste to be used as compost, eco enzyme and inorganic waste to be made into handicrafts such as flower vases, tables and decorative lamps every 4 weeks. The fourth most common form of participation is the form of skill and skill participation, namely using organic waste into compost and eco enzymes in Tanjung Pagar Village and using inorganic waste into handicrafts such as flower vases, tables and decorative lamps, and in Kelayan Selatan and Kelayan Tengah Village only limited collecting, sorting, selling and weighing waste to the waste bank and the public gets a savings book from the waste deposit.